Hands-On Artificial Intelligence with TensorFlow : Useful techniques in machine learning and deep learning for building intelligent applications /: Useful techniques in machine learning and deep learning for building intelligent applications. (2018) - Ziai, Amir; Dixit, Ankit
No abstract available